Кавитаційно-стійка Cr-Mn-N-V сталь для високотемпературної енергетики - Кучеренко, П.М.; Степанова, Т.В.; Шипицин, С.Я. (Physico-technological Institute of Metals and Alloys, 2023)
The results of investigations of the influence of type of strengthening of stable and unstable austenite Cr-Mn-N-V steels on the mechanism and degree of deformation strengthening and cavitational stability of steels are given.